ニュージーランド その2 : 愛、平和、自然、と哲学 - 城森, 満 (日本ニュージーランド学会誌, 1999)
January 1998, I visited New Zealand to teach Japanese language as a volunteer. at Onslow College Wellington, and also to learn from New Zealand people about their society, country, and school. The people who know the country, say as "Utopia" or "Man made Paradise" In '95 '96 I had experienced open minded, kind, and gentle treatment from so many people of this country. Why they have had it? From what point was it born? During my stay in NZ, I aquainted with many people, teachers, and students, Instead of teaching language, I learned so many, frank, straight, gentle, polite, and mild minds as human heart should be. I think it have originated not only from unsophisticated human heart but also embracing Maori problem in their body, high degree Social Welfare and raising their mind towards idealism. It will be proved with their Nature loving, Pacific, Antinuclear policy, and also our student's mild, kind, honest attitude, and breathing in, out their warm and dreamy air. While I was in NZ I could get so many youngest friends. "What is the Human Existance?" is the subject towarads 21 century. how we live and should be it is inevitable theme for us. I think.